Changes in the Nanostructure of Red Blood Cells in Intraoperative Blood Loss during Spinal Cord Surgery - V. V. Moroz; V. A. Sergunova; B. F. Nazarov; E. K. Kozlova; A. M. Chernysh; I. B. Vlasov (Общая реаниматология, 2013)
Objective: to study impairments in the nanostructure of red blood cells in blood loss during spinal cord surgery. Subjects and methods. The study enrolled 17 patients operated on at the Center of Neurosurgery, City Clinical Hospital Nineteen, for spinal cord pathology. Examinations were made in 3 patient groups: 1) a blood loss of less than 300 ml; 2) 600±200 ml; 3) 1500±200 ml. Images of fragments of the surface structure of red blood cell membranes were obtained using an atomic force microscope (NT-MDT). Results. The study showed the time course of changes in the index hi for the three patient groups. 24 hours after surgery, the first-order height h1 increased in all the patients. The time course of changes in h1, h2, and h3 was shown to have distinguishing characteristics in each of the above groups. In Group 1, the second- and first-order heights maximally rose on days 1 and 3, respectively. In Group 2, the first-order height maximally increased on day 1; in Group 3, there was a rise in all three orders on day 3. In Groups 1 and 2, the values of the nanostructure were close to the control ones on day 5 and in the 1500±200-ml blood loss group, hi was 5 times greater than the control on the same day. Conclusion. Spinal cord surgical blood losses give rise to systemic changes that directly affect red blood cells: they alter their membrane nanostructure, shape, and size. The membrane flicker increases and the characteristics of the spectrin matrix and aggregation of protein clusters change.